My first book of nature - Kuhn, Dwight (New York : Scholastic Inc., 1993)
Provides an introduction to growth, explaining how it occurs in such everyday things as guppies, apples, dogs, trees, and humans.
"Cartwheel Books"--T.p. verso.
Keywords: Growth -- Juvenile literature; Growth